Optimal Allocation and Control of Magnetorheological Dampers for Enhancing Seismic Performance of the Adjacent Structures Using Whale Optimization Algorithm - Xiufang Lin; Weiqing Lin (Shock and Vibration)
The control strategy for protecting adjacent structures from earthquake excitations is gaining increasing significance. In this study, to improve the seismic performance, a semiactive control strategy using magnetorheological (MR) dampers to couple the adjacent structures is proposed. In this control strategy, to fully exploit the performance of MR dampers, the allocation (including the locations and the number) and fuzzy logic controller (FLC) system of MR dampers are simultaneously optimally designed by whale optimization algorithm (WOA) with a special encoding scheme. Simulation results verify that WOA provides competitive performance compared with the other three metaheuristic algorithms in terms of solution quality and robustness. Compared with other semiactive control methods including on-off, linear quadratic regulator-clipped voltage law, and WOA-FLC (optimal allocation is not considered) methods, by using much less MR dampers, the proposed control strategy can exhibit more excellent overall performance in terms of reducing the seismic responses and mitigating pounding.